2018
DOI: 10.1108/ijwbr-09-2017-0063
|View full text |Cite
|
Sign up to set email alerts
|

Do implicit and explicit attitudes explain organic wine purchase intention?

Abstract: Purpose The purpose of this paper is to recognise the role of implicit and explicit attitudes on organic wine purchase intention and to segment consumers using these variables. Design/methodology/approach The authors conducted a two-part Web survey (n = 690) in Spain: an Implicit Association Test followed by a questionnaire on explicit attitudes, purchase intention and demographic data. Validity and reliability of these attitudes are contrasted using confirmatory factor analysis, attitude relationships with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…In this direction, behavior toward intention must emerge first. More precisely, behaviors are derived from specific intentions, which are impacted by the interaction of attitude, subjective norm and perceived behavioral control (Sarabia-Andreu and Sarabia-Sánchez, 2018). From the similar angle, many scholars (Vermeir and Verbeke, 2008) emphasized that intention to perform a behavior is positioned in the middle of this model and act as a crucial bridge between three antecedent determinants and final behaviors.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In this direction, behavior toward intention must emerge first. More precisely, behaviors are derived from specific intentions, which are impacted by the interaction of attitude, subjective norm and perceived behavioral control (Sarabia-Andreu and Sarabia-Sánchez, 2018). From the similar angle, many scholars (Vermeir and Verbeke, 2008) emphasized that intention to perform a behavior is positioned in the middle of this model and act as a crucial bridge between three antecedent determinants and final behaviors.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The study of Sarabia-Andreu and Sarabia-Sánchez [64] is the first to report on the potential influence of implicit and explicit attitudes on organic wine purchase intention. It has been found that only explicit attitudes significantly influence organic wine purchase intention.…”
Section: External Environmentmentioning
confidence: 99%
“…The constant search for new information aimed at maximizing and guiding the efficiency of companies means that research is increasingly focussed on identifying the segments and the consequent commercial strategies to be applied (Ellis and Caruana, 2018;Bauzà et al, 2005). The belief that the introduction on the label of information regarding organic processes used for wine production makes sense only if it is confirmed by a broad product demand (Sarabia-Andreu and Sarabia-S anchez, 2018;Lanfranchi et al, 2015;Antle, 1999). In the past decade, the demand for wine in Italy has recorded a significant contraction, linked to changes in food lifestyles and the evolution of consumption patterns (Pappalardo et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%